Dynamic functional impression technique for severely resorbed alveolar ridges. - Batista, A. U. [UNESP]; Carreiro, A da Fonte Porto; Souza, A A D de Araújo; Filho, J. N.; de Almeida, E. O. (My University, 2011)
The process of bone resorption can reduce the volume of the alveolar crest, which makes may make difficult impression taking of the alveolar tissue and the subsequent fit of a new denture. This clinical report describes a fast and simple technique for impressions of edentulous ridges to replace complete dentures, using a temporary tissue conditioner material on the denture base. The existing denture must cover the whole supporting area and should be in harmony with the adjacent oral structures. This technique reduces the number of steps involved and minimizes treatment time and expenses.